The Role of the National Sharia Arbitration Board in Alternative Dispute Resolution - Revano, Mochamad Ricky; Nasir, Muh.; Muchtar, Andhyka (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Sharia Arbitration Board is an institution whose mission is to resolve disputes peacefully based on Sharia principles without interference from public courts. This effort is made to provide legal certainty for legal subjects in dispute in Sharia economics. Law Number 30 of 1999 regulates that arbitration has the right to resolve problems and disputes related to civil law, including the economic, business, financial, trade, and industrial sectors by applying sharia principles. The method used is a qualitative descriptive and library research approach by analyzing documents, data, and information related to Basyarnas. This research shows that although Basyarnas' role in resolving sharia economic disputes is very important its decision position is binding on the parties.